1995
DOI: 10.1152/jappl.1995.79.6.2101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of baseline oxygenation on the ventilatory response to inhaled 100% oxygen in preterm infants

Abstract: We tested the hypothesis that the immediate (< 1 min) ventilatory response to 100% O2 in preterm infants, a test of peripheral chemoreceptor activity characterized by a decrease in ventilation due to apnea, is more pronounced at lower baseline O2 concentrations. We studied 12 healthy preterm infants [birth weight 1,425 +/- 103 (SE) g; study weight 1,670 +/- 93 g; gestational age 30 +/- 1 wk; postnatal age 27 +/- 7 days] during quiet sleep. The infants inhaled 15, 21, 25, 30, 35, 40, and 45% O2 for 5 min in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
3
3
0
1
Order By: Relevance
“…Furthermore, we found a significant correlation in this group between the rate of initial fall of the FHR and the severity of evolving hypotension during the episodes of umbilical cord occlusion. These findings are consistent with data indicating that preexisting hypoxemia increases peripheral arterial chemoreceptor activity in several settings (7,11,17) and strongly suggest that attenuation of the chemoreflex only occurs in response to episodes of relatively mild hypoxia (14,15).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we found a significant correlation in this group between the rate of initial fall of the FHR and the severity of evolving hypotension during the episodes of umbilical cord occlusion. These findings are consistent with data indicating that preexisting hypoxemia increases peripheral arterial chemoreceptor activity in several settings (7,11,17) and strongly suggest that attenuation of the chemoreflex only occurs in response to episodes of relatively mild hypoxia (14,15).…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested that the PB seen in premature infants may be of the episodic or cluster variety (Webber & Speck, 1981). Certainly, published recordings of PB in premature infants (Rigatto & Brady, 1972; Miller & DiFiore, 1995; Haider et al 1995) show an abrupt onset of breathing with little change in tidal volume before apnoea develops; this is similar to the episodic breathing pattern illustrated in Fig. 4.…”
Section: Discussionsupporting
confidence: 53%
“…Indeed, preterm infants with lower baseline oxyhemoglobin saturations are more prone to have apnea and periodic breathing. 18 Furthermore, exposure to an hypoxic gas mixture may lead to prolonged or recurrent apnea in infants. 19 Conversely, decreases in apnea density and periodic breathing ensued after inhalation of 100%.…”
Section: Discussionmentioning
confidence: 99%